HIV-related syndemic pathways and risk subjectivities among gay and bisexual men: a qualitative investigation. Issue 11 (2nd November 2017) - Adam, Barry D.; Hart, Trevor A.; Mohr, Jack; Coleman, Todd; Vernon, Julia
Abstract: Life history interviews were conducted with 40 gay and bisexual men to identify modes of syndemic experience and risk practice. Out of the interview narratives emerged one major and two minor modes of developmental pathway whereby syndemic conditions are navigated and expressed: (1) a combination of adverse childhood events with later episodes of depression and/or substantial substance use; (2) personal disruption that led to periods of depression and anxiety associated with the stresses of migration; and (3) a disorientation and an unravelling of life trajectory in the transition from family of origin to college or work. Risk practices fell into three high-risk modes: active and frequent engagement in condomless sex; unassertive deferment to a partner's initiation of condomless sex; and episodic risk combined with a risk reduction strategy. Three low risk modes were also identified: no recent condomlessness but multiple risk history in interview; a trajectory over time from high to low risk; and consistent low risk practice. These different modes of syndemic experience and risk management may have implications for identification of the effective HIV prevention tools that work best for different sets of men.